Politik Identitas Islam dan Pengaruhnya Terhadap Demokrasi di Indonesia - Anam, Haikal Fadhil (POLITEA, 2019)
The political identity of Islam emerged in a very large wave after the mobilization of time at the Jakarta elections in 2016. This has many implications for various aspects of State life, including the current democracy in Indonesia. In this case, Indonesia is a country that is still in the learning phase of democracy. The political influence of Islamic identity on democracy will make the nation split. This is backed by the strong narrative of the Political Islamic Group which at the end of the goal, wanted to establish the Islamic State. The future is political, will further heed and mobilize Muslims, as a majority, and rule out other religions.